Common Genetic Influences on Depression, Alcohol and Substance Use Disorders in Mexican-American Families - Olvera, RL (2011)
Multiple genetic and environmental factors influence the risk for both major depression and alcohol/substance use disorders. In addition, there is evidence that these illnesses share genetic factors. Although the heritability of these illnesses is well established, relatively few studies have focused on ethnic minority populations. Here, we document the prevalence, heritability and genetic correlations between major depression and alcohol and drug disorders in a large, community-ascertained sample of Mexican-American families. A total of 1,122 Mexican-American individuals from 71 extended pedigrees participated in the study. All subjects received in-person psychiatric interviews. Heritability and genetic and environmental correlations were estimated using SOLAR. Thirty-five percent of the sample met criteria for DSM-IV lifetime major depression, 34% met lifetime criteria for alcohol use disorders and 8% met criteria for lifetime drug use disorders. The heritability for major depression was estimated to be h(2)=0.393 (p=3.7×10(−6)). Heritability estimates were higher for recurrent depression (h(2)=0.463, p=4.0×10(−6)) and early onset depression (h(2)=0.485, p=8.5×10(−5)). While the genetic correlation between major depression and alcohol use disorders was significant (ρ(g)=0.58, p= 7×10(−3)), the environmental correlation between these traits was not. Although there is evidence for increased rates of depression and substance use in U.S.-born individuals of Mexican ancestry, our findings indicate that genetic control over major depression and alcohol/substance use disorders in the Mexican American population is similar to that reported in other populations.